An update on COVID-19 for the otorhinolaryngologist – a Brazilian Association of Otolaryngology and Cervicofacial Surgery (ABORL-CCF) Position Statement (2020)
Introduction We are facing a pandemic with a great impact worldwide, as a result of the rapid spread of the novel coronavirus (COVID-19). The medical community is still getting to know behavior of this virus and the consequences from a population point of view. All this knowledge is extremely dynamic, so some behaviors are still not well established. Otorhinolaryngologists have a central role in the management of this situation, in which they must assess the patient, avoid contamination to and by health professionals and other patients. Thus, the recommendations of the Brazilian Association of Otorhinolaryngology and Cervical-Facial Surgery (ABORL-CCF) have the main objective of reducing the spread of the new coronavirus during otorhinolaryngological care and assisting in the management of these patients. Methods Review of the main recommendations of national and international scientific societies, decisions by government agencies and class councils. The topics will be related to the general aspects of COVID-19, personal protective equipment, care in patient assistance, endoscopic exam routines and the management of sinonasal, otological and pediatric evaluations related to COVID-19. Results The use of personal protective equipment is considered crucial in routine ENT care. We recommend postponing appointments, exams and elective surgeries to reduce the spread of COVID-19. Similarly, we recommend changing routines in several areas of otolaryngology. Additionally, guidance is provided on the use of telemedicine resources during the pandemic period. Conclusions We are still at the beginning of the COVID-19 pandemic and scientific evidence is still scarce and incomplete, so these ABORL-CCF recommendations for otorhinolaryngologists may be updated based on new knowledge and the pattern of the new coronavirus spread.